Performance of dual-purpose corn varieties in Vientiane plains and Xiengkhuang plateau of Lao PDR: On-station and on-farm trials during wet season 2023 - Siviengkhek Hpommalath; Mponela, Powell; Zepeda Villarreal, E. Adair; Lopez-Ridaura, Santiago; Krupnik, Timothy Joseph (International Maize and Wheat Improvement Center, 2024)
This work was conducted as part of the CGIAR Initiative on Mixed Farming Systems. CGIAR research is supported by contributions to the CGIAR Trust Fund. CGIAR is a global research partnership for a food-secure future dedicated to transforming food, land, and water systems in a climate crisis.